Involvement of Nitric Oxide in Mitochondrial Activity and Brain Functions - Mayevsky, Avraham (British Journal of Healthcare and Medical Research, 2024)
Nitric Oxide (NO) is a critical regulator of cerebral blood flow as well as in the activity of the respiratory chain in the normal brain. The reduction of nitrate by red blood cells producing NO, plays a role in the regulation of vascular tone. In our study we found that Nitrite infusion increases CBF and decreased m ean arterial pressure. In our study we found that Nitrite has a regulatory role in brain circulation but not in the small intestine. Also, it seems that NO plays an important role in the autoregulation of CBF and mitochondrial function in the partially ischemic brain. Also it was found that NOS inhibitors demonstrate a beneficial on the brain cortex under status epilepticus induced by metrazol, implying that they may serve as anticonvulsant drugs. In the current study we concluded that NO may play a role during the initial phase of cortical spreading depression namely during the depolarization phase.